Future trends in fertility levels in Saudi Arabia until 2052 (The International Journal of Educational Sciences and Arts, 2025)
Future fertility trends are central to understanding demographic transitions and their impact on population structure in Saudi Arabia. While projections of fertility rates are available, deeper analysis through three scenarios (low, medium, high) remains essential.This study employs a descriptive-analytical approach to examine expected changes in the age structure between 2022 and 2052, using United Nations projections and the 2022 Census. The Spectrum program was applied to assess the impact of fertility change on population composition. In addition, the study explored the relationship between fertility and per capita GDP, and conducted statistical comparisons among administrative regions to identify regional disparities.The findings indicated a gradual decline in fertility rates, with varying effects across the scenarios. Under the low scenario, fertility is projected to drop to 1.36 children per woman, leading to a shrinkage in the population under 15 years, a decrease in the labor force, and an increase in the share of the elderly to 14% by 2052, thereby putting greater pressure on healthcare and social systems. In the medium scenario, a less sharp decline is expected (1.86 children), allowing more time to adapt to aging challenges, while the high scenario suggests a slower decline, resulting in relative stability in the age structure. The analyses further indicate that this demographic shift will be accompanied by rising life expectancy, highlighting the need for strategic planning to address the requirements of aging, particularly in the health sector.
Keywords: Fertility; Population Projections; Demographic Transitions